Gambaran Pengetahuan dan Sikap Masyarakat dalam Pencegahan Penularan TB Paru - Hara, Maria Kareri (Poltekkes Kemenkes Kupang, 2022)
Background: Pulmonary tuberculosis (TB) remains one of the major health challenges in Indonesia, especially in areas with high poverty and dense population. The role of community knowledge and attitudes is very important in preventing and controlling TB. Lack of community knowledge and awareness has the potential to increase the spread of Pulmonary TB. Objective: To describe the knowledge and attitudes of the community in preventing the transmission of Pulmonary TB in Temu Village, Kanatang District, East Sumba Regency. Method: The research design used descriptive. The population in this study were people living in Temu Village with a sample of 51 respondents using a saturated sample. The instrument used in this study was a questionnaire. Data analysis was descriptive. Results: The description of respondents' knowledge was predominantly in the good category of 22 people (43.1%) and respondents' attitudes were predominantly in the good category of 20 people (40%).